Miscibility of styrene/unsaturated polyester quasibinary systems: Unsaturated polyester chemical composition and molecular weight influence - Buffa, Fabián Alejandro (2006)
Unsaturated polyester prepolymers were synthesized with different chemical compositions and molecular weights. Cloud‐point curves (CPC) were measured in St‐UP quasibinary solutions, showing UCST behavior in all cases. The miscibility of the first UP samples series in St comonomer was enhanced when AA chemical comonomer concentration in UP prepolymer increased. In the second series, UP prepolymer miscibility increased with the molecular weight up to a maximum and, after that, the miscibility decreased. A thermodynamic analysis of experimental CPCs was performed using the Flory‐Huggins (F‐H) theory for polydisperse polymer solutions. A simple relationship between the interaction parameter and the temperature inverse could fit the measured CPCs in wide concentrations and molecular weight ranges. In the temperature interval where this fit took place, the positive enthalpic contribution to the interaction parameters determined the miscibility dependence with temperature in both UP sample series. The St‐UP miscibility behavior was also correlated with UPs structural chemical parameters as: (a) the final HO and HOOC high polar groups concentration, (b) the chain backbone polar adipate and phthalate groups concentration, and (c) the UP size dependent mixing entropy. All these parameters are molecular weight dependent.